Experimental Phase Equilibrium Data for Rotenone in Supercritical Carbon Dioxide - Lima, Jéssica Carvalho; De Araújo, Paulo Cardozo Carvalho; Dos Santos Croscato, Gilson; De Almeida, Ossalin; Cabral, Vladimir Ferreira; Ferreira-Pinto, Leandro [UNESP]; Cardozo-Filho, Lucio (American Chemical Society (ACS), 2019)
In this paper, we report data for the phase transition of the binary [rotenone (1) + CO2 (2)] system obtained visually using the static synthetic indirect method and a variable-volume cell at temperatures between 303 and 343 K and pressures near 20 MPa. The molar fraction varied from 1.0 × 10-5 to 2.75 × 10-5. For a molar fraction of rotenone greater than 2.75 × 10-5, the phase transition data could not be measured at pressures of 30 MPa because of the experimental limitations of the equipment. The pressure limitation arose because of the difficulty in solubilizing the system where the solubilization occurs close to or above the limits of the experimental apparatus (30 MPa). The transition of the system was identified as the solid-fluid type, and the phase transition profiles are similar. The Peng-Robinson equation of state (PR-EoS) with the classical mixing rule was used to correlate the experimental data to theory, and excellent agreement was found between the experimental and calculated values.